IMPLEMENTASI PEMBUATAN PENAMPUNG AIR HUJAN (PAH) UNTUK BANGUNAN RUMAH TINGGAL - Endang S Hisyam; Desy Yofianti; Ferra Fahriani; Yayuk Apriyanti; Revy Safitri (Fakultas Teknik, Universitas Bangka Belitung, 2022)
Community service activities in Jada Bahrin Village, are service activities carried out routinely by the Civil Engineering Department, Bangka Belitung University. In 2021, activities in this village are planned again. Initial information about the condition of the village and what the current needs of the village are is the basis for planning community service activities. Rainwater Reservoir (PAH) is a solution to overcome the limited availability of water in the dry season for residential buildings in Jada Bahrin Village. With the existence of PAH, the community is expected to be able to take advantage of the rainwater that is stored during the rainy season and use it during the dry season to meet water needs during the dry season